MEDIA SOSIAL FACEBOOK SEBAGAI SARANA KOMUNIKASI KOMUNITAS HONDA C50-C70-C90 SOLO RAYA - Farul Ardy Pratama (Solidaritas, 2018)
Abstrack This research is a qualitative descriptive that tries to describe the community communication facilities Honda Honda C50-C70-C90 Solo Raya. Using Miles and Huberman's interactive analysis model, The means of communication such as interactions between members to pour ideas about Honda C series motorcycle. Interactions between members of a community going extensive exchange of information i.e. sharing, business and kopdar Facebook Social Media members use to enhance solidarity and to know each other. Sharing information, knowledge and experience, between members of the fosters an attitude of caring and mutual regard among members of one another. So Facebook social media Honda C Series adds to the solidarity and togetherness classic motorcycle lovers. To be able to communicate, know each other and create an expectation based on impressions or information that has been obtained. In the Facebook Honda C50 C70 C90-Solo-Raya Community recognizes these members with fellow members communicate through Facebook.Keywords: Media, Community, Facebook, means of communication